Reasons behind Students' Silence to Teacher's Directive Utterances: A Case Study on A Lower Secondary School in Yogyakarta (NOBEL: Journal of Literature and Language Teaching, 2022)
Classroom interaction is identified to engage students in responding and interacting with teachers and other students. However, one problem that usually interferes with teacher-student interaction is unpredictable students’ reactions in interpreting the teacher’s utterances. The present research investigated several reasons for students’ responses to teachers’ directive utterances. To reach the objective, a case study was applied. Three eighth-grade students in a Yogyakarta lower secondary school were selected to participate in this study. The data were collected through observation and interviews. Meanwhile, the data analysis was based on Miles’ interactive model. The results of this study show that internal and external variables affect the students’ responses during English classes. A lack of vocabulary and needing extra time to guess are the internal variables to understanding the teacher’s intention. Meanwhile, unfavorable classroom atmospheres resulting from noisy students, noisy next-door classes, and noisy vehicles outside are the external variables that disturb the students’ attention and understanding of the teacher’s directive utterances. The results of this research reveal significant implications for students’ attitudes, as they rarely develop their interaction due to internal and external factors. Thus, the condition requires the teacher’s role as an active language user.